PENGARUH ROM (Range of Motion) TERHADAP KEKUATAN OTOT EKSTREMITAS PADA PASIEN STROKE NON HEMORAGIC - Anggriani Anggriani; Zulkarnain Zulkarnain; Sulaiman Sulaiman; Roni Gunawan (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2018)
Stroke is one of the serious health problems in modern life today. The prevalence of stroke increases with age. The World Health Organization (WHO) stipulates that stroke is a clinical syndrome with symptoms of global brain dysfunction that can cause death or abnormalities to persist for more than 24 hours, without other causes except vascular disorders which can cause a person's reduced mobility due to muscle strength downhill. This study aims to determine the effect of ROM (range of motion) on limb muscle strength in non-Hemaoragic stroke patients at H. Adam Malik General Hospital, Medan. Quasi-experimental research design with a sample of 90 people. Univariate and bivariate data analysis using the Wilcoxon test. The significance of hand muscle strength before and after administration of ROM is 0,000. This means that there are differences in hand muscle strength before and after administration of ROM. The significance of leg muscle strength before and after administration of ROM is 0,000. This means that there are differences in leg muscle strength before and after administration of ROM. This proves that ROM influences the strength of the respondent's hand and leg muscles. Hospitals should set standard operating procedures for special handling of ROM so that the results obtained can be maximal and uniform for all muscle strength problemsKeywords: ROM, limb muscle strength, hands, feet